Comparison of the Efficacy of Trichoderma and Bacillus Strains and Commercial Biocontrol Products against Grapevine Botryosphaeria Dieback Pathogens - Natalia Langa-Lomba; Vicente González-García; M. Eugenia Venturini-Crespo; José Casanova-Gascón; Juan J. Barriuso-Vargas; Pablo Martín-Ramos (Agronomy, 2023)
Grapevine trunk diseases (GTDs) cause significant yield losses worldwide and limit the lifespan of vineyards. In the last few years, using biological control agents (BCAs) for pruning wound protection has become a promising management strategy for the control of these pathologies. This study aimed to compare the antifungal activities of a grapevine-native Trichoderma harzianum isolate and a high-potential Bacillus velezensis strain against two pathogenic Botryosphaeriaceae species in artificially inoculated, potted, grafted plants under controlled greenhouse conditions, taking three commercial biocontrol products (based on T. atroviride I-1237, T. harzianum T-22, and Bacillus subtilis BS03 strains) as a reference. To reproduce certain field conditions more realistically, inoculation of the protective agents and the pathogens was conducted simultaneously immediately after pruning instead of allowing the BCAs to colonize the wounds before pathogen inoculation. Significant differences in necrosis lengths were detected for both Neofusicoccum parvum- and Diplodia seriata-infected plants, and a remarkable protective effect of Bacillus velezensis BUZ-14 was observed in all cases. Trichoderma-based treatments showed different efficacies against the two pathogenic fungi. While the three tested BCAs resulted in significant reductions in vascular necrosis caused by N. parvum, they did not significantly reduce D. seriata infection compared to the untreated inoculated control. The B. subtilis strain was not effective. The reported results provide support for the potential Bacillus velezensis may have for pruning wound protection against Botryosphaeriaceae fungi, encouraging its evaluation under natural field conditions.